(untitled) (Conference on English Language Teaching, 2023)
The toxic food environment is impacted by several food business. Entrepreneurs in the food industry must increase their concern for an ecological consciousness that requires them to pay attention to environmental changes that have an impact on society. Based on Ecolinguistics and Cognitive Linguistics, this study seeks to determine how the ecological insights possessed by tertiary-level students are disclosed in their writings, food business plans. The descriptive-qualitative technique was used in this investigation. The business plans are the main source of information for ecological insights that are revealed via the usage of words or phrases. The research shows that students concerned about consumer health, employment opportunities, online support services, and trash management. It is necessary to increase the average ratio of ecological words or phrases. Some students’ ecological awareness and understanding have not yet been completely developed in terms of how they use language to communicate. Fortunately, there is a rising proportion of ecological terms or phrases in the students’ compositions as compared to the prior survey.